Characterization Of Clayey Ceramic Body Used For Roofing Tile Fabrication - Carlos Maurício Fontes Vieira (The Minerals, Metals and Materials Society, 2006)
In the present work a ceramic body, fabricated using a mixture of clays and sand, for roofing tiles, produced in Campos dos Goytacazes, north of the State of Rio de Janeiro in Brazil, was characterized. Characterization was performed by X-ray diffraction, thermo analysis, chemical analysis, particle size distribution determination and plasticity. In addition, technological properties related to water absorption, linear shrinkage and flexural rupture strength were determined in samples fired at 700, 900 and 1100oC. The results showed that the investigated ceramic body has satisfactory plasticity and presents a refractory behavior during firing due to the predominantly kaolinitic nature of the clays.